Understanding FAHFAs: From structure to metabolic regulation - Brejchova, Kristyna; Balas, Laurence; Paluchova, Veronika; Brezinova, Marie; Durand, Thierry; Kuda, Ondrej (Progress in lipid research, 2020)
The discovery of branched fatty acid esters of hydroxy fatty acids (FAHFAs) in humans draw attention of many researches to their biological effects. Although FAHFAs were originally discovered in insects and plants, their introduction into the mammalian realm opened new horizons in bioactive lipid research. Hundreds of isomers from different families have been identified so far and their role in (patho) physiological processes is currently being explored. The family of palmitic acid esters of hydroxy stearic acids (PAHSAs), especially 5-PAHSA and 9-PAHSA regioisomers, stands out in the crowd of other FAHFAs for their anti-inflammatory and anti-diabetic effects. Beneficial effects of PAHSAs have been linked to metabolic disorders such as type 1 and type 2 diabetes, colitis, and chronic inflammation. Besides PAHSAs, a growing family of polyunsaturated FAHFAs exerts mainly immunomodulatory effects and biological roles of many other FAHFAs remain currently unknown. Therefore, FAHFAs represent unique lipid messengers capable of affecting many immunometabolic processes. The objective of this review is to summarize the knowledge concerning the diversity of FAHFAs, nomenclature, and their analysis and detection. Special attention is paid to the total syntheses of FAHFAs, optimal strategies, and to the formation of the stereocenter required for optically active molecules. Biosynthetic pathways of saturated and polyunsaturated FAHFAs in mammals and plants are reviewed together with their metabolism and degradation. Moreover, an overview of biological effects of branched FAHFAs is provided and many unanswered questions regarding FAHFAs are discussed.
Keywords: Inflammation; estery; Lipid mediators; diabetes mellitus; kolitida; zánět; Fatty Acids; Diabetes Mellitus; PAHSA; zvířata; Humans; Biological effects; Total synthesis; molekulární struktura; mastné kyseliny; Colitis; Esters; FAHFA; lidé; Molecular Structure; Animals